Teaching Strategies And Moral Value In “Freedom Writers” By Richard Lagravanese - Murniasih, Murniasih (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
The purpose of the research is to analyze Teaching Strategies and Moral Value in the movie “Freedom Writers” by Richard Lagravanese. This research is descriptive qualitative by content analysis. The data source was taken from scene in the Freedom Writers movie. The object of this research is movie Freedom Writers directed by Richard LaGravenese. The instrument of the research is teaching strategies and moral value. In this research the researcher uses flow model analysis stated by Miles and Huberman to analyze the data, the activities in analyzing data are: (1) Displaying the data related of teaching techniques conducted by researcher and reducing unnecessary data from the movie. (2) Classifying the form of teaching techniques employed by the character in the Movie Freedom Writers. (3) Analyzing and interpreting the kinds of teaching techniques employed by character in the movie Freedom Writers. (4) Drawing conclusion from the data analysis and giving suggestion. The researcher at this stage in data processing is Drawing conclusion from the data analysis and giving suggestion in the form of a thesis. the writer found 16 total of dialogues teaching strategies in “Freedom Writers” movie by Richard Lagravanese which the highest percentages is Sociocultural – interactive strategies which consist of 7 dialogues (41%), Affective Strategy consist of 4 dialogues (24%), Cognitive Strategy consist of 3 (23%) and the last as the lowest is Compensatory Strategy consist of 2 dialogues (12%). the writer also found 17 total of dialogues moral value in “Freedom Writers” movie by Richard Lagravanese which the highest percentages is social moral which consist of 9 dialogues (53%), individual moral of 7 dialogues (41%), the last as the lowest is religion moral consist of 1 dialogue (6%).